2015
DOI: 10.1016/j.apjtb.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, serotype diversity and antibiogram of Salmonella enterica isolated from different species of poultry in India

Abstract: A B S T R A C TObjective: To study the occurrence and serotype diversity of Salmonella isolates in different species of poultry (chicken, emu and duck) and determine their resistance pattern against various antibiotics of different classes. Methods: About 507 samples comprising 202 caecal contents and 305 fecal samples from chicken, emu and duck were processed for isolation of Salmonella enterica. Salmonellae were isolated and detected by standard protocol of ISO 6579 Amendment 1: Annex D. Genetic confirmation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
(37 reference statements)
8
30
0
Order By: Relevance
“…According to statistical evaluations, all samples showed statistical differences (P < 0.01) in terms of antibiotic resistances and susceptibilities (Table 4). These findings are in agreement with previous studies on chicken meat from Iran (Dallal et al, 2010;Sodagari et al, 2015), India (Mir et al, 2015), Turkey (Yildirim et al, 2011) andEgypt (Abd-Elghany et al, 2015), Iraq (Harb et al, 2018).…”
Section: Antibiotic Resistance Of Salmonella Spp Isolatessupporting
confidence: 93%
“…According to statistical evaluations, all samples showed statistical differences (P < 0.01) in terms of antibiotic resistances and susceptibilities (Table 4). These findings are in agreement with previous studies on chicken meat from Iran (Dallal et al, 2010;Sodagari et al, 2015), India (Mir et al, 2015), Turkey (Yildirim et al, 2011) andEgypt (Abd-Elghany et al, 2015), Iraq (Harb et al, 2018).…”
Section: Antibiotic Resistance Of Salmonella Spp Isolatessupporting
confidence: 93%
“…The results from the study indicated that OmpF protein of Salmonella typhimurium is a strong candidate for developing recombinant vaccine against salmonellosis in poultry. and Davies, 2010;Mir et al, 2015) and easy transmission of Salmonella bacteria through food and water. This organisms seems to be associated with gut of poultry, hence consumption of contaminated poultry meat, egg and its products consumption and contact with infected birds are the major transmission route to humans (Adak et al, 2005).…”
Section: Issn: 2319-7706 Volume 7 Number 05 (2018)mentioning
confidence: 99%
“…Many of the Salmonella serotypes that are most prevalent in humans are also common in poultry (Van Duijkeren et al, 2001). The emergence of antimicrobial resistant Salmonella is mostly associated with the non-therapeutic use of various classes of antimicrobials in large quantities in food animals (Marshall and Levy, 2011;Mir et al, 2015; Wales and Davies, 2015). Therefore, this study was undertaken to characterize antimicrobial resistance of Salmonella spp strains occur in farm and chicken eggs carriage.…”
Section: Introductionmentioning
confidence: 99%